Extended thymectomy via subxiphoid uniportal Video-Assisted Thoracoscopic Surgery: A case report. (March 2021) - Joalsen, Ivan; Christian, David; Rosalie, Amy; Angga, Made
Highlights: Minimally invasive thymectomy is the primary surgical means for myasthenia gravis. Subxiphoid VATS method has the benefit of less blood loss and shorter hospital stay. Subxiphoid surgical port placement eliminates postoperative intercostal neuralgia. Subxiphoid uniportal thymectomy is safe and feasible for selected patients. Abstract: Introduction and importance: Myasthenia gravis (MG) is a well-known disease in adults, but the prevalence in children population is low. One treatment option is thymectomy. Transsternal procedure have been the primary approach, but recent trends lean toward minimally invasive technique with triportal and, recently, uniportal thoracoscopic method. This is related to the suggested less blood loss and hospital length of stay. Case presentation: Hereby we report a case of a 4-year-old boy suffering from Juvenile Myasthenia Gravis (JMG) with thymic hyperplasia who underwent extended thymectomy via subxiphoid uniportal Video-Assisted Thoracoscopic Surgery (VATS) in our hospital. Pathology evaluation reported a case of thymic hyperplasia. The postoperative outcome was uneventful and satisfactory. Clinical discussion: Subxiphoid uniportal approach for thymectomy is relatively new and has not been widely reported. It is important to highlight its advantages and disadvantages compared to other means for thymectomy. Conclusion: Subxiphoid uniportal VATS is a safe and feasible approach for thymectomy.